PELATIHAN KEWIRAUSAHAAN BERBASIS PARIWISATA UNTUK MENDORONG KEMANDIRIAN EKONOMI MASYARAKAT DESA ADAT BUALU - I Made Sujana; Putu Ratna Windusara Putri; Fahmi Tanjung; I Made Wisnu Wardana (Yayasan Nusantara Hasana Berdikari, 2023)
Tourism-based entrepreneurship development is one of the strategic approaches to improving economic independence within rural communities. Bualu Traditional Village, located in a strategic tourism area of Badung Regency, possesses significant economic potential that can be developed through local tourism-based entrepreneurial activities. However, community members still face challenges related to business management, product innovation, digital marketing utilization, and sustainable business planning. This community service program aimed to enhance the entrepreneurial capacity of the Bualu Traditional Village community through tourism-based entrepreneurship training. The methods included socialization, training sessions, mentoring activities, business plan preparation workshops, and program evaluation. A total of 40 participants consisting of MSME actors, youth groups, women’s groups, and productive community members took part in the program. The results indicated significant improvements in participants’ knowledge of entrepreneurship, business management, digital marketing, tourism product development, and business planning. The program successfully strengthened community capacity in utilizing tourism-related economic opportunities and contributed to sustainable economic independence.